2012
DOI: 10.5588/ijtld.10.0754
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice concerning tuberculosis in a growing industrialised area in Myanmar

Abstract: More effective communication strategies towards factory workers are needed to increase workers' knowledge about transmission and reduce stigma. Employers should be sensitised to protect employees with TB and invest in preventive activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
1
20
0
5
Order By: Relevance
“…In a study conducted in Vietnam, more than 50% of the study participants reported fear of being known as people with TB in the community [ 22 ]. Similar findings (both quantitative and qualitative) on the presence of TB stigma were also reported in studies conducted in neighboring countries in the region [ 23–25 ]. Some of the variations in prevalence could be attributed to the different study designs used, data collection tools used, populations sampled, and the cultural life that differed within and across communities [ 21 , 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…In a study conducted in Vietnam, more than 50% of the study participants reported fear of being known as people with TB in the community [ 22 ]. Similar findings (both quantitative and qualitative) on the presence of TB stigma were also reported in studies conducted in neighboring countries in the region [ 23–25 ]. Some of the variations in prevalence could be attributed to the different study designs used, data collection tools used, populations sampled, and the cultural life that differed within and across communities [ 21 , 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…Social discrimination for fear of disease dissemination is a universal TB-associated stigma [21,22]. It is a noted fact that people avoid and even reject the interaction with TB patients, leading to their social exclusion and difficulty in finding the marital match [23,24]. Unfortunately, such attitudes seem to be worsening with an increasing level of education, income, and awareness of TB [8,20,25].…”
Section: Discussionmentioning
confidence: 99%
“…Workers’ fear of social isolation due to contraction of the disease and associated stigma observed in this study is a common phenomenon worldwide [ 19 – 21 ]. Stigma combined with poor knowledge of TB delays its diagnosis and causes treatment non-adherence, and may act as an important barrier to service utilization.…”
Section: Discussionmentioning
confidence: 99%